Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Touching feeling: Affect, pedagogy, performativity - Sedgwick, Eve Kosofsky (Duke University Press Books, 2003)
A pioneer in queer theory and literary studies, Eve Kosofsky Sedgwick brings together for the first time in Touching Feeling her most powerful explorations of emotion and expression. In essays that show how her groundbreaking work in queer theory has developed into a deep interest in affect, Sedgwick offers what she calls "tools and techniques for nondualistic thought," in the process touching and transforming such theoretical discourses as psychoanalysis, speech-act theory, Western Buddhism, and the Foucauldian "hermeneutics of suspicion." In prose sometimes somber, often high-spirited, and always accessible and moving, Touching Feeling interrogates—through virtuoso readings of works by Henry James, J. L. Austin, Judith Butler, the psychologist Silvan Tomkins and others—emotion in many forms. What links the work of teaching to the experience of illness? How can shame become an engine for queer politics, performance, and pleasure? Is sexuality more like an affect or a drive? Is paranoia the only realistic epistemology for modern intellectuals? Ultimately, Sedgwick's unfashionable commitment to the truth of happiness propels a book as open-hearted as it is intellectually daring.
Keywords: approches et analyses; arts; autobiographie; discipline; queer; émotions; études littéraires